Control of Adjacent Buildings Using Shared Tuned Mass Damper. (2017) - Guenidi, Z.; Abdeddaim, M.; Ounis, A.; Shrimali, M.K.; Datta, T.K.
Abstract: Seismic control of adjacent buildings has received considerable attention in recent years because of two reasons: i) for the control of the response of the two buildings simultaneously by a single control device and ii) for the reduction of the possibility of interaction between the two buildings. Various types of coupling devices have been introduced and their effectiveness in controlling the responses of the adjacent building is studied. Out of the different types of the coupling devices, MR damper is one which is widely investigated. In this paper, the responses of the two buildings are controlled by using two strategies: i) a shared tuned mass damper (TMD) and ii) a hybrid system using both a TMD and a MR damper. The shared TMD is mounted such that it can effectively control the responses of both buildings and it is tuned to the fundamental frequencies of (i) the coupled structure and (ii) the two adjacent buildings vibrating separately. The shared TMD has the obvious advantage that the two separate TMDs are not required to control the two buildings separately. The response control includes the control of the top story displacement, base shear and maximum drift. Results of the study show that i) a shared TMD can provide adequate response reduction compared to that obtained by using two TMDs separately, ii) the frequency ratio between the two adjacent building is the most important parameter which dictates the response reduction, iii) the hybrid control provides a significant improvement in response reduction over that obtained by a shared TMD alone.